Compact Solid-State Marx Generator for Repetitive Applications - Pinjari, N.; Bindu, S. (Engineering, Technology & Applied Science Research, 2020)
The Marx generator plays a vital role in a pulsed power system. In this paper, a modified compact bipolar output pulse solid-state Marx generator topology is developed. A three-stage prototype is designed and tested, in which pulse width, polarity, and peak voltage of the output pulse are made variable. It is possible to generate either positive or negative pulses with less rise time. Various components which affect the repetitive frequency of the developed Marx generator are evaluated. Analysis reveals that the total time period TO is a function of capacitor charging time. This is been validated experimentally by operating the Marx generator for different pulse repetition frequencies. The type of charging method solely controls the charging time of the capacitor and hence the repetition frequency.